(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
Tanzania has a vast hydro power potential which has not been tapped. Among such potentials is Kapologwe Waterfalls along Kala River. Therefore, developing mini-grids in these populations can relieve the load to the electricity load to the national grid. However, limited research, on such potentials has hindered this development. In this work the potential of Kala River, as a source of hydropower, to meet electricity demand for the surrounding villages, was investigated. Hydrological analysis of the un-gauged Kala River was done in order to determine the hydraulic head and the quantity of water. This encompassed measuring the river terrain, wetted cross sectional area and flow velocity. The weir, sediment tank, and power house positions and elevations were also determined using the Grid Positioning System. Given that the Kala River was not gauged, the Karl Pearson's Coefficient was used to assess the relationship between the gauged Kiwira River and the ungauged Kala River, and the Weibull plotting technique was utilized to establish the flow duration curve for the ungauged Kala river watershed. The results show a net hydraulic head of 605.15 meters and a mean flow rate of 1.542m3. The turbine that was chosen had a mean efficiency of 0.8 to 0.9. Kapologwe's water falls in the Kala River have a 72378.07kW realized power potential, which is sufficient for the creation of a mini-hydropower project. The study suggests that in order to harness this hydropower potential for the socio-economic development of the catchment's settlements, a cross flow turbine must be installed near the Kapologwe waterfalls.